Technological devices in order Picking System: Bibliographic review - Barreto, Clarice Gonçalves; Machado, Ricardo Luiz (Brazilian Journal of Production Engineering, 2022)
Orders have been in high demand at the warehouse as a result of shifting consumer behavior. The activity of choosing and collecting orders is regarded as the most important. These are the most expensive and time-consuming tasks. Many professionals have turned to technology equipment to improve their performance in these activities. This article presents a literature review with the goal of identifying which devices are found in scientific studies for the purpose of meeting order picking demand, as well as identifying the factors studied for each one, as well as identifying insights and gaps for future research or development of new devices. For this, 101 articles with some device in the order picking were examined. These items were separated and classified based on their intended usage and qualities. As a result, researchers and decision makers may become acquainted with the devices under consideration and comprehend how they operate. This research concludes that interest in the issue has increased significantly in the previous two years, and that various elements must be considered before selecting the device, which are: layout, SKU, deployment model, and implementation.